Experimental Investigation on Cavitating Flow Induced Vibration Characteristics of a Low Specific Speed Centrifugal Pump - Bo Gao; Pengming Guo; Ning Zhang; Zhong Li; Minguan Yang (Shock and Vibration)
Cavitating flow developing in the blade channels is detrimental to the stable operation of centrifugal pumps, so it is essential to detect cavitation and avoid the unexpected results. The present paper concentrates on cavitation induced vibration characteristics, and special attention is laid on vibration energy in low frequency band, 10–500 Hz. The correlation between cavitating evolution and the corresponding vibration energy in 10–500 Hz frequency band is discussed through visualization analysis. Results show that the varying trend of vibration energy in low frequency band is unique compared with the high frequency band. With cavitation number decreasing, vibration energy reaches a local maximum at a cavitation number much larger than the 3% head drop point; after that it decreases. The varying trend is closely associated with the corresponding cavitation status. With cavitation number decreasing, cavitation could be divided into four stages. The decreasing of vibration energy, in particular cavitation number range, is caused by the partial compressible cavitation structure. From cavitation induced vibration characteristics, vibration energy rises much earlier than the usual 3% head drop criterion, and it indicates that cavitation could be detected in advance and effectively by means of cavitation induced vibration characteristics.